DESKRIPSI KETERAMPILAN PSIKOMOTORIK SISWA SMA TARUNA BUMI KHATULISTIWA PADA MATERI LARUTAN ELEKTROLIT DAN NON-ELEKTROLIT - Widowati, Nimas; Enawaty, Eny; Rasawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to describe the psychomotor skills of students class XI SCIENCE Taruna Bumi Khatulistiwa Senior High School on material electrolyte and non-electrolyte solution. The form of this research is descriptive with case study method using measurement technique and direct communication. The subjects were students Taruna Bumi Khatulistiwa Senior High School in XI IPA 1 academic year 2016/2017 consisted of 27 students. The data collection tool used in this research is the students' psychomotor rating sheet on the practicum of electrolyte and non-electrolyte solution. The results showed that students' psychomotor skills in assembling electrolyte test equipment including very good category, good and enough were 87.87%, 9.09%, and 3.03% respectively, and the aspect of testing the electrolyte solution in the very good category , good, enough and not good is 5757%, 30.3%, 9.09% and 3.03% respectively. This shows that students class XI SCIENCE Taruna Bumi Khatulistiwa Senior High School has been able to assembling electrolyte test equipment and testing the electrolyte solution.Keywords: Psychomotor Skills, Electrolyte and Non-Electrolyte SolutionÂ